2017
DOI: 10.1021/acs.langmuir.7b03226
|View full text |Cite
|
Sign up to set email alerts
|

Flat Drops, Elastic Sheets, and Microcapsules by Interfacial Assembly of a Bacterial Biofilm Protein, BslA

Abstract: Protein adsorption and assembly at interfaces provide a potentially versatile route to create useful constructs for fluid compartmentalization. In this context, we consider the interfacial assembly of a bacterial biofilm protein, BslA, at air-water and oil-water interfaces. Densely packed, high modulus monolayers form at air-water interfaces, leading to the formation of flattened sessile water drops. BslA forms elastic sheets at oil-water interfaces, leading to the production of stable monodisperse oil-in-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…The matrix of this bacterium consists of proteins called TasA and TapA [63,64] besides a secreted polysaccharide of high molecular weight [65]. The assemblage of the mature biofilm also requires the presence of a coating protein called biofilm BsIA, previously known as YuaB [65][66][67]. Haggag and Timmusk [68] demonstrated that the bacteria Paenibacillus polymyxa colonizes plant roots, forming structures that look like biofilms and thus protecting the roots against diseases caused by phytopathogens.…”
Section: Formation Of Biofilms and Quorum Sensingmentioning
confidence: 99%
“…The matrix of this bacterium consists of proteins called TasA and TapA [63,64] besides a secreted polysaccharide of high molecular weight [65]. The assemblage of the mature biofilm also requires the presence of a coating protein called biofilm BsIA, previously known as YuaB [65][66][67]. Haggag and Timmusk [68] demonstrated that the bacteria Paenibacillus polymyxa colonizes plant roots, forming structures that look like biofilms and thus protecting the roots against diseases caused by phytopathogens.…”
Section: Formation Of Biofilms and Quorum Sensingmentioning
confidence: 99%
“…In addition, the process of air bubble stabilisation reduces the formation of ice crystals, which ensures smooth consistency of the product. The use of the Bs1A protein may allow manufacturers to reduce saturated fats content, and thus calorific value of ice cream [31,69]. The ability to form foams can be much greater for class II than for class I proteins.…”
Section: The Use Of Hydrophobins In Various Fieldsmentioning
confidence: 99%
“…Ponadto proces stabilizacji pęcherzyków powietrza ogranicza powstawanie kryształków lodu, co zapewnia gładką konsystencję produktu. Zastosowanie białka Bs1A może pozwolić producentom zmniejszyć zawartość tłuszczów nasyconych, a więc i kaloryczność lodów [31,69]. Zdolność do formowania pian może być znacznie większa dla białek klasy II niż klasy I. Ta zależność niesie ze sobą potencjalne nowe zastosowania w przemyśle spożywczym.…”
Section: Zastosowanie Hydrofobin W Różnych Gałęziach Przemysłuunclassified
“…Another strategy is through interfacial tension driven evolution of droplet morphology where the local accumulation of surface-active emulsifiers at interfaces can partially change the droplet curvature. [25][26] A widely used approach is microchannel confinement, which offers unrivalled performance for the controlled generation of droplets of varying size, shape, morphology, internal structure and chemistry. 8,27 Using microfluidics to control local flows, the flexible design of microscale geometries and the applicability of auxiliary forces allow a high degree of control over the manipulation of individual droplets.…”
Section: Introductionmentioning
confidence: 99%